Evaluation and Management of B3 Waste Sludge via the Sludge Oil Recovery (SOR) Program at PT. X Plaju - Nurdiasna, Widya Reza; Septiariva, Iva Yenis; Suryawan, I Wayan Koko; Sari, Mega Mutiara; Ulhasanah, Nova (Jurnal Teknik Kimia dan Lingkungan, 2023)
With the ever-increasing need for waste management solutions, PT. X Plaju is one of the entities that contribute to B3 waste production, a waste type characterized by its explosive, flammable, reactive, corrosive, and toxic properties. This research centers on the evaluation and management of B3 waste sludge, particularly at PT. X Plaju. The institution implements two licensed B3 waste control programs: the Sludge Oil Recovery (SOR) and used lubricant utilization programs. The SOR program, which focuses on recovering components from oil deposits or sludge, operates under the recovery principle. This study showcases the importance of the oil component in the oil sludge, emphasizing that it must constitute more than 20% of the total volume to be deemed suitable for refinery production. Our findings highlighted a water content of 28.32% within the waste oil sludge. Additionally, the ultimate analysis showcased carbon, hydrogen, and nitrogen compositions of 85.99%, 13.42%, and 0.21%, respectively, while the density was measured at 0.85 gr/cc. This research offers insights into the waste management practices of PT. X Plaju, emphasizing the potential of the SOR program in managing B3 waste effectively.